The Fly [videorecording (DVD)] - Hedison, David, 1929-2019-; Hedison, David, 1929-2019-; Owens, Patricia, 1925-2000; Price, Vincent, 1911-1993; Marshall, Herbert, 1890-1966; Langelaan, George, 1908-1969 (20th Century Fox Home Entertainment, 2013)
Experimental scientist Andre Delambre attempts to transfer matter through space, using himself as the test subject. But things go horrifically wrong when a common housefly buzzes into the machine, resulting in two grotesque man-fly hybrids. Now, with the head of a fly and a wing in place of one of his arms, Andre desperately hopes that he, his wife Helene and his brother Francois can capture the other mutant - the human-headed, one-armed fly - in hopes of reversing the experiment. Special feature: Audio commentary with actor David (Al) Hedison.